A spatially explicit assessment of climate change vulnerability in the agricultural sector of the Union of the Comoros - Bourgoin, Clément; Parker Louis; Martínez Valle, Armando Isaac; Mwongera, Caroline; Läderach, Peter R.D. (2016)
Situated between Mozambique and Madagascar, the Union of the Comoros is one of the world’s poorest countries. Heavy dependence on agriculture, complicated by high population density and a lack of governance has led to mismanagement of natural resources and land degradation. Additionally, the country faces several environmental risks, including drought, soil erosion, and flooding. With two cropping seasons and a favorable microclimate for agriculture, there is real potential to increase production of banana (Musa acuminata), cassava (Manihot esculenta) and tomato (Lycopersicon esculentum). To improve food security and create income opportunities for the rural poor, these value chains are the focus of projects funded by the International Fund for Agricultural Development (IFAD). This study analyses potential impacts of projected climate change on the selected value chains and utilizes modelling approaches and GIS tools to make preliminary recommendations on how to manage the climate risks and increase the resilience of small-scale farmers.